2016
DOI: 10.1016/j.fertnstert.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor is expressed in human sperm cells and is involved in sperm motility

Abstract: Angiotensin II type 2 receptor is present in human semen and may be involved in the control of sperm motility. In-depth understanding of the proteins involved in sperm motility can help to elucidate the role of these proteins in male infertility as well as to establish new biomarkers for male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 48 publications
1
36
0
2
Order By: Relevance
“…Apart from the significant correlation with motility, the present study revealed no significant correlation with sperm concentration or with morphology. Gianzo et al, (), on the other hand, detected a significant positive correlation between AT2R expression and sperm concentration but not with morphology. This difference as regards sperm concentration could be attributed to the heterogeneous nature of their study population as regards fertility status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Apart from the significant correlation with motility, the present study revealed no significant correlation with sperm concentration or with morphology. Gianzo et al, (), on the other hand, detected a significant positive correlation between AT2R expression and sperm concentration but not with morphology. This difference as regards sperm concentration could be attributed to the heterogeneous nature of their study population as regards fertility status.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, its action was believed to be independent of calcium‐mediated signals (Kohn, Muller, et al, ; Wennemuth et al, ). It was also detected on the equatorial and post‐acrosomal regions of the sperm head in humans, which suggests its involvement in sperm functions essential for reproduction (Gianzo et al, ). In the current study, AT2R was located not only on the sperm head including the acrosomal cap, but also on the midpiece and the tail, though the level of expression differed in the studied groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ATR1 activation increases intracellular concentrations of cyclic adenosine monophosphate (cAMP) and calcium, two key secondary messengers of sperm capacitation (Vedantam, Rani, Garg, & Suresh, 2014). In human sperm, ATR2 controls sperm motility (Gianzo et al, 2016). Whether or not tACE participates in this angiotensin-mediated regulation of sperm function is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, intensity was positively correlated with sperm motility. Angiotensin II type 2 receptor has been investigated using flow cytometry in human spermatozoa (Gianzo et al., ). The expression of this protein was reduced in asthenozoospermic patients.…”
Section: Single‐cell Analysis In Sperm Proteomics: Flow Cytometrymentioning
confidence: 99%